GREP w pracy redaktora – wprowadzenie do zagadnienia - Poradecki, Mateusz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The paper considers the use of the Global Regular Expression Print tool in the Adobe InDesign application. The paper shows the results of the research on the utilisation of this tool in editors’ work. It presents examples of common mistakes which can be automatically corrected using the Find/ Change tool with the GREP function. The paper also indicates threats connected with making new mistakes when the tool is used without extreme care or in a wrong order. The conclusion is that the GREP tool cannot be used without human supervision as languages are too complicated and not all situations can be predicted.